Electrical Engineering Education, Research, and Innovation: An Indian, Asian, and Global Perspective - Dr. Pravin R. Choube (Asian Education Index, 2026)
Electrical Engineering (EE) has played a foundational role in industrial development, technological innovation, and economic growth across the world. From power generation and transmission to electronics, automation, communication systems, and emerging areas such as renewable energy and smart grids, electrical engineering remains central to modern society. This paper presents a comprehensive review of the evolution, current status, and future direction of electrical engineering education, research, and innovation from an Indian, Asian, and global perspective. The study examines historical development, curriculum trends, research output, industry–academia collaboration, and emerging technological domains. By comparing regional strengths and challenges, the paper highlights India’s growing role within Asia and the global electrical engineering ecosystem. The findings suggest that while developed economies continue to lead in advanced research and innovation, India and other Asian countries are rapidly closing the gap through policy reforms, expanding higher education capacity, and increased investment in science and technology.
Keywords: Electrical Engineering; Engineering Education; India; Asia; Global Perspective; Power Systems; Research Trends